1991
DOI: 10.1111/j.1600-051x.1991.tb00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin isotype distribution of locally produced autoantibodies to collagen type I in adult periodontitis

Abstract: Production of antibodies to collagen type I was analyzed by means of an enzyme-linked immunospot (ELISPOT) assay in patients with chronic adult periodontitis (AP) before and after periodontal hygiene treatment. Anti-collagen type I antibody-secreting cells were found among mononuclear cells enzymatically eluted from inflamed gingiva in 9 of 15 patients with untreated AP and in 4 of 14 hygiene-treated patients with a varied isotype distribution. A notably high prevalence of IgG and IgM isotypes was observed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…It is suggested that while T lymphocytes and polymorphonuclear cells dominate in the early stages of plaque accumulation and gingivitis, B cells dominate in more advanced lesions, with a higher degree of soft tissue destruction and bone loss (9,36). As is seen in periodontal disease (5,15,20,36), B cells are activated in the synovial tissue in patients with arthritis, leading to a spontaneous secretion of Igs (IgG, IgA, and IgM) (1). This lymphocytic response may lead to the subsequent formation of immune complexes, which are capable of inducing a spectrum of inflammatory mediators (17,34).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that while T lymphocytes and polymorphonuclear cells dominate in the early stages of plaque accumulation and gingivitis, B cells dominate in more advanced lesions, with a higher degree of soft tissue destruction and bone loss (9,36). As is seen in periodontal disease (5,15,20,36), B cells are activated in the synovial tissue in patients with arthritis, leading to a spontaneous secretion of Igs (IgG, IgA, and IgM) (1). This lymphocytic response may lead to the subsequent formation of immune complexes, which are capable of inducing a spectrum of inflammatory mediators (17,34).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-collagen antibody has been consistently detected and suggested to be involved in gingival tissue destruction. 11,12,37 In addition to their well-known role in antibody production, B cells also have the determinative role as antigen-presenting cells (APCs) in the generation of T-cell-mediated immune responses. 38 Recent studies have shown that B cells are critical in the pathogenesis of T-cell-mediated autoimmune diseases.…”
Section: and 10 µG/ml) After 24 Hours Of Incubation Cells Were Hmentioning
confidence: 99%
“…15,16 In addition, several studies reported on higher levels of antibodies to collagen type 1 in gingival tissue than in serum. [17][18][19] Several factor-binding sites that might be involved in the regulation of IL-10 were identified in the IL-10 promoter. [20][21][22] The IL-10 promoter contains several single nucleotide polymorphisms (SNPs) among which the -1087 G/A SNP (sometimes referred to as À1082 G/A) was associated with differences in IL-10 promoter activity and IL-10 production.…”
Section: Introductionmentioning
confidence: 99%